The puzzle of internal audit function budget toward specialist auditor choice and audit fees: does family ownership matter? Malaysian evidence. - AL Qadasi, Adel Ali; Abidin, Shamharir; Al Jaifi, Hamdan Amer Ali (Emerald Publishing Limited, 2018)
Purpose – This study is motivated by the lack of internal audit function (IAF) research and by the call for research on the impact of dominant owners such as family shareholders on audit fees and the demand for audit quality. This study aims to examine the impact of the IAF budget on the selection of industry-specialist auditors and on audit fees, particularly in companies with family-controlled shareholders, a feature unique to Malaysia. Design/methodology/approach – Data of Malaysian-listed companies during the period 2009-2012 are used. To examine the relationships, logit and ordinary least square regressions are used. Several additional analyses are conducted to assess the robustness of the main results, including alternative measures of specialist auditor and family ownership, endogeneity problems and self-selection bias. Findings – The results show that the IAF budget is positively related to hiring industry-specialist auditors and audit fees. However, family companies are less likely to support the positive association between IAF costs and engage specialist auditors than non-family companies. In addition, a complementary association between the costs of IAF and audit fees for both family and non-family companies was found. Finally, the results show that there is a negative association between family ownership and the ratio of IAF costs to audit fees, suggesting that family companies rely more upon external auditing than internal auditing. Originality/value – The contribution of this study is to provide an empirical evidence about the trade off between IAF and both industry-specialist auditors and audit fees with considering the moderating impact of family-ownership shareholdings. This issue is yet to be examined, and it provides implications for policymakers and practitioners, as it offers insights into the importance of investing in IAF toward hiring industry-specialist auditors and pricing the audit services